Chinese-British commercial conflicts in Shanghai and the collapse of the merchant-control system in late Qing China, 1860-1906 - Motono, E; Motono, Eiichi (1994)
﻿ During the 1860s, Chinese merchants reestablished their commercial organizations which are recorded as Guilds (hanghui) in the sources compiled under the guidance of the Qing local government officials. From the decade until the end of the 1880s, English sources emphasized the solidarity of the commercial organizations of Chinese merchants and their superiority to the British mercantile community in the commercial conflicts in which they were engaged. However, from the 1890s, English sources ceased to complain the strength of the commercial organizations of Chinese merchants, and, at the same time, Chinese sources emphasized the existence of a crisis in which Chinese merchants were losing their solidarity. Moreover, the Qing local government officials endeavoured to maintain their control over the commercial organizations of Chinese merchants, an attempt which led to the birth of Chinese chambers of commerce in the early twentieth century. Former studies, which dealt with the superiority of the Chinese merchants' organizations to the British mercantile firms in the 1860s and the 1870s, or the birth of the Chinese bourgeoisie and the activities of their commercial organizations in the early twentieth century, have not been able to reveal what happened in the commercial organizations of the Chinese merchants during the late nineteenth century. The solidarity of the Chinese merchant organizations was maintained by the rule that no one could claim the privilege of doing business without paying the Lijin tax imposed upon it, and the collapse of their solidarity began with when some Chinese compradors and merchants found it possible to do their business without keeping this rule by means of cooperating British mercantile firms, who enjoyed key privi- leges under the Treaties as regards non-payment of the Lijin tax and investment on the basis of limited liability. By intensively analyzing three commercial conflicts between prominent Chinese merchant organizations and British mercantile firms that took place in Shanghai between the end of the 1870s and the end of the 1880s, this study reveals how, and under what conditions some Chinese compradors and merchants could do their business without observing the afore-mentioned rule governing the Chinese merchants' organizations, what happened when British mercantile people became aware what their compradors or cooperative Chinese merchants had doing behind their back, and how these developments contributed to the end of the old-style merchant class, and the beginning of a bourgeoisie. By bringing these facts to the surface for analysis, this study shows a little known aspect of the Chinese society and tries on the basis to re-evaluate an aspect of concept of "China's response to the Western impact."